EL CONCEPTO DE DEMOCRACIA: UN ANÁLISIS MULTIDIMENSIONAL - Hernández, Diego Mauricio (Novos Estudos Jurídicos, 2021)
This article starts with the semantic decomposition of the phrase demokratos, which states a subordination of “kratos” (government) to “demos” (people), and analyzes the concept of democracy from a multi-dimensional key. In order to elaborate on the concept of democracy, an analytical distinction was established around three dimensions of government subordination to the people: democracy is understood as (i) the government of the people, (ii) the government by the people, and (iii) the government for the people or the government that serves the people. This kind of analysis can establish a good state of art for contemporary discussions on democratic theory, and determine the main ways to improve the existing democratic government systems.